Another Analysis of the EEOCC “Four-Fifths” Rule - Boardman, Anthony E. (Management Science, 1979)
Federal guidelines provide grounds for determining when a racial, ethnic or sex group has experienced discrimination in selection or promotion. This paper assumes that a predetermined number of people are selected or promoted and presents a simple model that computes the exact probabilities of type I and type II errors, that is, concluding adverse impact when none exists and concluding no adverse impact when it does, in fact, exist.